2008
DOI: 10.2984/1534-6188(2008)62[1:pcotmc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Population Characteristics of the Mangrove Crab Scylla serrata (Decapoda: Portunidae) in Kosrae, Federated States of Micronesia: Effects of Harvest and Implications for Management1

Abstract: Apparent declines in abundance of mangrove crabs Scylla serrata (Forsskål, 1755) in Kosrae, Federated States of Micronesia, have prompted concern regarding long-term persistence of this important cultural and economic resource. To support development of effective management strategies, we gathered basic biological information about mangrove crabs on this island, where S. serrata is the only mangrove crab species present. In particular, we were interested in understanding movement patterns and evaluating spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 24 publications
3
27
0
3
Order By: Relevance
“…In unfished populations, female mud crabs can be three-fold outnumbered by males, for example in Kosrae, Micronesia the male: female ratio can be as high as 3:1 (Bonine et al, 2008). Similar ratios have been reported from other studies (Heasman, 1980).…”
Section: Sex Ratios and Densitysupporting
confidence: 71%
See 1 more Smart Citation
“…In unfished populations, female mud crabs can be three-fold outnumbered by males, for example in Kosrae, Micronesia the male: female ratio can be as high as 3:1 (Bonine et al, 2008). Similar ratios have been reported from other studies (Heasman, 1980).…”
Section: Sex Ratios and Densitysupporting
confidence: 71%
“…In general, crabs ([100 mm CW) that live in enclosed habitats such as narrow mangrove-fringed creeks, normally do not move more than 1 km (Hill, 1975;Perrine, 1978;Hyland et al, 1984;Bonine et al, 2008), whereas in southern Moreton Bay, Queensland, crabs that are found in open environments like intertidal flats in open bays show larger movement (average 3.7 km) (Hyland et al, 1984). It is suggested that these different distances of routine movement (daily movements, e.g., foraging activity) are dependent on the availability of alternative feeding grounds at high tide.…”
Section: Movement Habitat Use and Activity Of Adult Mud Crabsmentioning
confidence: 99%
“…Ewel (2007) has investigated mean carapace width of S. serrata at different locations in Kosrae. Allometric relationship between carapace width and weight in mangrove crabs (S. serrata) on Kosrae of Macronesia has been reported by Bonine et al (2008). Studies on carapace width and weight relationships, relative condition factor of mud crabs S. serrata and S. tranquebarica have been made by Mohapatra et al (2010) in Chilka lagoon.…”
Section: Introductionmentioning
confidence: 94%
“…Menurut La Sara (2010) Scylla serrata pada fase juvenil memiliki lebar karapas <70 mm, fase muda (lebar karapas dari 70 -<120 mm) dan fase dewasa (lebar karapas >120 mm). Menurut Bonine et al (2008) kepitng bakau (Scylla serrata) jantan dewasa kelamin rata-rata ketika lebar karapas mulai ukuran 90-110, sedangkan kepitng betina mulai matang gonad pada rata-rata ukuran lebar karapas 80-120 mm. Ilustrasi distribusi frekuensi lebar karapas kepiting bakau di Teluk Bintan disajikan pada Gambar 3.…”
Section: Analisis Status Biologi Kepiting Bakauunclassified